Cerebellar functional disruption and compensation in mesial temporal lobe epilepsy - Peng, Yiqian; Wang, Kangrun; Liu, Chaorong; Tan, Langzi; Zhang, Min; He, Jialinzi; Dai, Yuwei; Wang, Ge; Liu, Xianghe; Xiao, Bo; Xie, Fangfang; Long, Lili (Frontiers in Neurology, 2023)
Background: Cerebellar functional alterations are typical in mesial temporal lobe epilepsy (MTLE) and contribute to cognitive decline in patients. This study aimed to advance our knowledge regarding the cerebellar functional alterations of MTLE. Methods: Thirteen patients with left MTLE (LTLE), 17 patients with right MTLE (RTLE), and 30 healthy controls (HC) from an ongoing prospective cohort participated in this study. Functional magnetic resonance imaging data were collected during a Chinese verbal fluency task. Group-independent component analysis was applied to segment the cerebellum into six functionally separated networks. Functional connectivity between cerebellar networks, the cerebellar activation maps, and the centrality parameters of cerebellar regions was compared between the three groups. For cerebellar functional profiles with significant differences, we calculated their correlation with clinical features and neuropsychological scores. Result: Compared to patients with LTLE and HC, patients with RTLE presented higher functional connectivity between cerebellar default mode network and cerebellar oculomotor network and weaker functional connectivity from cerebellar frontoparietal network to cerebellar dorsal attention network (p < 0.05, FDR-corrected). In patients with LTLE, the degree centrality of the right cerebellar lobule III was significantly increased compared to HC and patients with RTLE (p < 0.05, FDR-corrected). Higher functional connectivity between cerebellar default mode network and oculomotor network and lower degree centrality of right cerebellar lobule III was correlated with worse Information Test performance. Conclusion: Cerebellar functional profiles were altered in MTLE and was correlated with long-term memory in patients.